2019
DOI: 10.3389/fped.2019.00141
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Natural Killer/T-Cell Lymphoma, Nasal Type: Basic Science and Clinical Progress

Abstract: Extranodal natural killer (NK)/T-cell lymphoma, nasal type (NNKTL) has very unique epidemiological, etiologic, histologic, and clinical characteristics. It is commonly observed in Eastern Asia, but quite rare in the United States and Europe. The progressive necrotic lesions mainly in the nasal cavity, poor prognosis caused by rapid local progression with distant metastases, and angiocentric and polymorphous lymphoreticular infiltrates are the main clinical and histologic features. Phenotypic and genotypic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
140
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(156 citation statements)
references
References 108 publications
2
140
0
8
Order By: Relevance
“…These 2 groups of patients are currently closely monitored. In the event of recurrence of the disease, lymphoma specimens will be tested for molecular biology-related indicators, and new treatments such as chemotherapy combined with monoclonal antibodies to programmed cell death protein 1 or programmed cell death ligand 1; histone deacetylase inhibitors; monoclonal antibody to CD38; or immunomodulator lenalidomide will be administered according to the molecular tests and literature findings 17 . To date, we have 2 clinical trials registered for relapsed and refractory ENKTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 2 groups of patients are currently closely monitored. In the event of recurrence of the disease, lymphoma specimens will be tested for molecular biology-related indicators, and new treatments such as chemotherapy combined with monoclonal antibodies to programmed cell death protein 1 or programmed cell death ligand 1; histone deacetylase inhibitors; monoclonal antibody to CD38; or immunomodulator lenalidomide will be administered according to the molecular tests and literature findings 17 . To date, we have 2 clinical trials registered for relapsed and refractory ENKTL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown promising results of treatments with monoclonal antibodies against cluster of differentiation (CD)52 and the protein deacetylase inhibitor romidepsin 15 , 16 . Furthermore, many molecular targets for ENKTL are being introduced 17 . Although newer regimens have demonstrated positive outcomes in the treatment of ENKTL, they still do not always meet patients’ needs.…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, nasal lymphoma is known as extranodal natural killer/T-cell lymphoma, nasal type (26). The lymphoma originates from either natural killer cells or γδ T-cells, both of which express CD56 (26).…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, nasal lymphoma is known as extranodal natural killer/T-cell lymphoma, nasal type (26). The lymphoma originates from either natural killer cells or γδ T-cells, both of which express CD56 (26). Conversely, a B-cell phenotype comprises 40% of feline nasal lymphomas, and a T-cell phenotype comprises 47% (27).…”
Section: Discussionmentioning
confidence: 99%
“…The lymphoma cells originate from either NK cells or γδ T cells [ 3 ]. T cell receptor gene rearrangement is observed in 10–35% of patients [ 4 ]. Therefore, in the latest World Health Organization classification, these lymphomas are referred to as ENKTLs, to reflect their putative cellular origins from NK cells and T cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%